Ответ:
Пошаговое объяснение:
a) у = 6х⁵ - 4х² + 2
y' = 6(x⁵)' -4(x²)' +(2)' = 6*5x⁴ -4*2x +0= 30x⁴-8x
b) у = еˣ * (x3 + 1)
[ (uv)' = vu' +v'u ; u = еˣ; v = (1+x³)]
y' = (1+x³) (еˣ)' + еˣ(1+x³) = еˣ(1+x³) +еˣ(1)' + еˣ (x³)'=
еˣ (1+x³) +0 +еˣ * 3x² =
= еˣ (1+x³ +3x²)
2)
![\int\limits^2_1 {x^{5} } \, dx = \frac{x^{6} }{6 } I_{1}^{2} = \frac{2^{6} }{6} -\frac{1^{6} }{6} = \frac{21}{2} \int\limits^2_1 {x^{5} } \, dx = \frac{x^{6} }{6 } I_{1}^{2} = \frac{2^{6} }{6} -\frac{1^{6} }{6} = \frac{21}{2}](https://tex.z-dn.net/?f=%5Cint%5Climits%5E2_1%20%7Bx%5E%7B5%7D%20%7D%20%5C%2C%20dx%20%3D%20%5Cfrac%7Bx%5E%7B6%7D%20%7D%7B6%20%7D%20I_%7B1%7D%5E%7B2%7D%20%20%3D%20%5Cfrac%7B2%5E%7B6%7D%20%7D%7B6%7D%20-%5Cfrac%7B1%5E%7B6%7D%20%7D%7B6%7D%20%20%3D%20%5Cfrac%7B21%7D%7B2%7D)